The Association Between Working Duration and Driver Characteristics with Subjective Fatigue Among Dump Truck Drivers - Ummi Lailatul Maghfiroh (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Work fatigue is a major risk factor contributing to occupational accidents in the mining industry, particularly among dump truck drivers who are exposed to long working hours, high physical demands, and harsh environmental conditions. This study aimed to analyze the relationship between work duration and driver characteristics, including age, body mass index (BMI), and length of service, with subjective fatigue levels among dump truck drivers at PT X mining site. A cross-sectional study design was employed involving 40 dump truck drivers as respondents. Subjective fatigue was assessed using the Industrial Fatigue Research Committee (IFRC) questionnaire, while relationships between variables were analyzed using the Chi-square test. The results showed that most drivers worked more than 8 hours per day (90%), were in early adulthood (72.5%), had 6–10 years of work experience (50%), and were classified as overweight based on BMI (50%). The majority of respondents experienced low levels of fatigue (80%). Bivariate analysis revealed that BMI was the only variable significantly associated with subjective fatigue (p = 0.048), while work duration, age, and length of service showed no significant relationship. In conclusion, although overall fatigue levels were relatively low, body mass index emerged as a significant predictor of fatigue. Therefore, fatigue prevention strategies focusing on nutritional intervention, health monitoring, and safety education are strongly recommended to maintain driver performance and reduce accident risk.